2007
DOI: 10.1111/j.1439-0434.2007.01261.x
|View full text |Cite
|
Sign up to set email alerts
|

A Real‐time PCR Assay for Quantitative and Accurate Assessment of Fungicide Effects on Mycosphaerella graminicola Leaf Blotch

Abstract: A real-time PCR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Although all fungicide treatments resulted in a significant DNA reduction, compared with a nontreated control, later applications of prothioconazole, at 7 to 10 dpi, resulted in a high loss of efficiency ( 50%). These results are in agreement with those reported by (Godwin et al, 1999) and (Guo et al, 2007), namely that prothioconazole has a significant inhibitive effect against spore germination and postgermination, and could have a good curative effect against M. graminicola when applied at up to 20% of the latent period. However, most fungicides work best when applied early in the infection cycle, prior to visual symptom expression (O'Reilly et al, 1988).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although all fungicide treatments resulted in a significant DNA reduction, compared with a nontreated control, later applications of prothioconazole, at 7 to 10 dpi, resulted in a high loss of efficiency ( 50%). These results are in agreement with those reported by (Godwin et al, 1999) and (Guo et al, 2007), namely that prothioconazole has a significant inhibitive effect against spore germination and postgermination, and could have a good curative effect against M. graminicola when applied at up to 20% of the latent period. However, most fungicides work best when applied early in the infection cycle, prior to visual symptom expression (O'Reilly et al, 1988).…”
Section: Discussionsupporting
confidence: 83%
“…The association of specific chemistries and a fluorescent reporter molecule (TaqMan chemistry) with PCR has permitted the development of real-time PCR (Schena et al, 2004). This technique is an accurate and reliable tool for many phytopathological studies (Guo et al, 2006(Guo et al, & 2007Fraaije et al, 1999;Schena et al, 2004). Real-time PCR analysis, also referred to as quantitative PCR (qPCR), can provide a deeper insight into host-pathogen interactions by detecting the primary inoculum, general infection level and genotypes, depending on the specific target gene.…”
mentioning
confidence: 99%
“…These results are in agreement with those reported by Godwin et al . and Guo et al ., namely that prothioconazole has a significant inhibitive effect against spore germination and post‐germination, and could have a good curative effect against M. graminicola when applied at up to 20% of the latent period. However, most fungicides work best when applied early in the infection cycle, prior to visual symptom expression .…”
Section: Discussionmentioning
confidence: 98%
“…The association of specific chemistries and a fluorescent reporter molecule (TaqMan chemistry) with PCR has permitted the development of real‐time PCR . This technique is an accurate and reliable tool for many phytopathological studies . Real‐time PCR analysis, also referred to as quantitative PCR (qPCR), can provide a deeper insight into host–pathogen interactions by detecting the primary inoculum, general infection level and genotypes, depending on the specific target gene.…”
Section: Introductionmentioning
confidence: 99%
“…Real‐time PCR has been widely described as a precise, reproducible and reliable method to quantify M. graminicola before the appearance of visible symptoms during the incubation period 7, 17–19. The results for the untreated control in the present two experiments showed that the isolate ST38, which produced the lowest disease symptoms, always had a DNA amount higher than the two other isolates TO249 and TO252.…”
Section: Discussionmentioning
confidence: 55%